PRMT1 promotes the tumor suppressor function of p14ARF and is indicative for pancreatic cancer prognosis. (17th May 2021) - Repenning, Antje; Happel, Daniela; Bouchard, Caroline; Meixner, Marion; Verel‐Yilmaz, Yesim; Raifer, Hartmann; Holembowski, Lena; Krause, Eberhard; Kremmer, Elisabeth; Feederle, Regina; Keber, Corinna U; Lohoff, Michael; et al.
Abstract: The p14 ARF protein is a well‐known regulator of p53‐dependent and p53‐independent tumor‐suppressive activities. In unstressed cells, p14 ARF is predominantly sequestered in the nucleoli, bound to its nucleolar interaction partner NPM. Upon genotoxic stress, p14 ARF undergoes an immediate redistribution to the nucleo‐ and cytoplasm, where it promotes activation of cell cycle arrest and apoptosis. Here, we identify p14 ARF as a novel interaction partner and substrate of PRMT1 (protein arginine methyltransferase 1). PRMT1 methylates several arginine residues in the C‐terminal nuclear/nucleolar localization sequence (NLS/NoLS) of p14 ARF . In the absence of cellular stress, these arginines are crucial for nucleolar localization of p14 ARF . Genotoxic stress causes augmented interaction between PRMT1 and p14 ARF, accompanied by arginine methylation of p14 ARF . PRMT1‐dependent NLS/NoLS methylation promotes the release of p14 ARF from NPM and nucleolar sequestration, subsequently leading to p53‐independent apoptosis. This PRMT1‐p14 ARF cooperation is cancer‐relevant and indicative for PDAC (p ancreatic d uctal a denoc arcinoma) prognosis and chemotherapy response of pancreatic tumor cells. Our data reveal that PRMT1‐mediated arginine methylation is an important trigger for p14 ARF 's stress‐induced tumor‐suppressive function. Synopsis: Genotoxic stress is known to cause nucleolar release of the tumor suppressor and p53 regulator p14 ARF . Here, this redistribution is shown to be depend on p14 ARF arginine methylation by PRMT1 methyltransferase. p14 ARF is a novel interaction partner and substrate of PRMT1. Genotoxic stress causes PRMT1‐dependent methylation of p14 ARF and major changes in its interaction network. Arginine methylation in its nuclear/nucleolar localization sequence releases p14 ARF from nucleolar sequestration and promotes p53‐independent apoptosis. The cooperation between PRMT1 and p14 ARF is indicative for pancreatic cancer prognosis and chemotherapy response. Abstract : Arginine methylation in the nuclear/nucleolar localization sequence regulates intracellular redistribution and promotion of p53‐independent apoptosis by of p14 ARF .